Self-Paced Learning Practices during Educational Disruption in a Public Higher Education Institution - Delma Jean V. Abad; Eduardo M. Abad (East Asian Journal of Multidisciplinary Research, 2023)
Educational disruption happens due to Covid -19 Pandemic which made the learning institutions create policies to ensure that the education continues and the quality of learning is not compromised. This results in adhering to students Self-Paced Learning (SPL) mode of education. 46 Tertiary students who were purposively selected served as the respondents In this undertaking. SPL was investigated along the challenges and coping strategies the students experienced as an aftermath of the sudden paradigm shift in education. This research utilized a Case Study as it collected data on a specific event that affects how individuals react and change their behaviour, and the situation based on the respondents’ perspectives was analyzed. Semi-structured interviews and a Focus Group discussion were employed to gather data from the respondents. The data were explored to identify recurring concepts, collapsed similar themes, and interpreted the results through Inductive vivo coding. The Top-level, Middle and Third Codes were identified and plotted into codebook. There are four (4) Top Level Codes disclosed on challenges on Self-Paced composed of: Challenges on Submission of Learning Materials, Challenges on the Use of Learning Technology and Challenges on Schooling at Home.Further, a contextualized Andragogical Instructional Framework on Self-Paced Learning was designed from the sentiments identified as an output of this study.